The role of affective factors in the english language proficiency of fourth-year students registered in the B.A in english language teaching and in the B.A in modern languages emphasis in French and English at the Foreign Language Department of the University of El Salvador, semester I, 2018 - Deras Guevara, Katherine Andrea; Monterrosa Juárez, Prisila Elizabeth; Abrego Vásquez, Josué Rolando (2024)
This research project expects to highlight the main affective factors that influence the learning process of a foreign language. According to different studies and authors such as: Douglas Brown, Underhill, A. (1999) Arnold, J. (2000) and many others; this influence can be considered undeniable. Besides the existing literature mentioned about affective factors in English Language learning, it is appropriate to analyze the importance of these affective variables in a foreign language classroom since there are many reasons that justify of affectivity in learning. Because, factors can help teacher to understand students and to be conscious of students’ learning. Students can be influenced by their own feelings and if these are negative, learning will be diminished, regardless of teachers’ efforts. In this way, it is essential not only to know how to detect the behaviors and attitudes of students and know what is behind them, but also to stimulate and encourage positive ideas and beliefs focused on obtaining real and effective goals in the process of learning. For that reason, this work will be carried out in the Foreign Language Department at the University of El Salvador. In this way, this research aims to describe the most prominent affective factors that may interfere in the students’ learning process. Finally, once argued the need to consider emotions in the process of foreign language learning, some recommendations are proposed to help teachers to enhance the affective variables for encouraging and facilitating the learning process.